Controlling pool depth during VAR of Alloy 718. (July 2016) - Lopez, F; Beaman, J; Williamson, R; Evans, D
Abstract: A longtime goal of superalloy producers has been to control the geometry of the liquid pool in solidifying ingots. Accurate pool depth control at appropriate values is expected to result in ingots free of segregation defects. This article describes an industrial VAR experiment in which a 430mm (17 in) diameter Alloy 718 electrode was melted into a 510mm (20 in) ingot. In the experiment, the depth of the liquid pool at the mid-radius was controlled to three different set-points: 137 mm (nominal), 193 mm (deep) and 118 mm (shallow). At each level, the pool depth was marked by a power cutback of several minutes. The ingot was sectioned and longitudinal slices were cut out. Analysis of the photographed ingot revealed that accurate control was obtained for both the nominal and deep pool cases, while the third one was not conclusive.